Quasi-retractive representation of solution sets to stochastic inclusions. (1997) - Kisielewicz, Michal
Abstract : Continuous dependence and retraction properties of solution sets to stochastic inclusions x t − x s ∈ ∫ s t F τ ( x τ ) d τ + ∫ s t G τ ( x τ ) d ω τ + ∫ s t ∫ ℝ n H τ, r ( x τ ) v ˜ ( d τ, d r ) are considered.